Analysis of Tensile Strength of Jute and Coconut Coir Reinforced Polymer Matrix Composite - Berliana Maulani Naziha; Putri Ayu Nurmakhmuda; Utiya Hikmah (Journal of Applied Sciences and Advanced Technology, 2022)
A Composite is a mixture of two or more elements that are physicochemical and different from one another which can produce new products with better properties. As technology advances, conventional composite materials began to be replaced with polymer materials. One way of making polymer composites is to use polyester resin with natural fiber reinforcement. Coconut coir is a natural fiber with a high cellulose content and can produce high lignin is the cause of coconut coir having stiffer properties than other natural fibers. It is this rigid nature that causes coconut coir to be widely ogled by the textile industry. Another example that is often used as a reinforcement for polymer composites is jute fiber. Jute fiber is a natural fiber with high quality derived from the extraction of plant stems with a multicellular structure. This research is about measuring the tensile test of composites with a polyester resin matrix reinforced by jute and coconut fiber.